The choice between state- and time-dependent price rules - Klas Fregert (Lund University, School of Economics and Management, Department of Economics, 2008)
Large review costs lead to time-dependent price setting rules. State-dependent rules become more likely when there is an increase in: set-up costs, the variability of the equilibrium price or the efficiency loss associated with being away from equilibrium.
Keywords: E31; E32; 330; time-dependent price rule; state-dependent price rule